WANITA INSPIRATIF : BIOGRAFI SUMIYATI KHILYATUN HASANAH 1997-2023 - Farantika, Regita; Meri Erawati; Refni Yulia (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This study examines the biography of Sumiyati Khilyatun Hasanah from 1997 to 2023. The research problem addressed in this thesis is: What were the factors that led to Sumiyati Khilyatun Hasanah being named an Inspirational Woman in 2023? The purpose of this research is to describe Sumiyati Khilyatun Hasanah's career journey and her contributions in the social field. The writing of this thesis utilizes the historical method, which is composed of four stages:First, heuristics, or data collection from various sources that are relevant, utilizing primary sources such as documents, interview reports, and individuals directly involved in the matter. Second, source criticism, which involves testing the authenticity of the data to determine whether it is relevant to the writing or not. Third, interpretation, which involves explaining the data obtained so that it can support this writing. And fourth, historiography, which is the process of writing the research results in the form of a scientific paper or thesis.The results of the study show that Sumiyati Khilyatun Hasanah's career journey from 1997-2023 includes several stages: founding a Quranic Education Park (TPQ) and the Rimbo Bujang Islamic Boarding School in 1997, being actively involved in PKK and BKMT activities from 2005-2011, entering politics in 2014, and establishing the Inayah Multi Business Center (IMBC). Sumiyati's contributions in the social field include activities such as supporting orphans and leadership, as well as her involvement in converting members of the Suku Anak Dalam (SAD) to Islam. Sumiyati was named an Inspirational Woman in 2023.